Regulating the Environmental Impact of Direct Investment in Developing Countries: The Need to Shift from a Command-andControl Mechanism to a Multi-stakeholder Approach - Woldeyohannes, Mekdes Tadele (Bahir Dar University Journal of Law, 2022)
Investment promotion occupies a prominent place in the development policies ofdeveloping and least developed countries. Yet it poses challenges to the achievementof sustainable development by undermining social development and exposing theenvironment to degradation. This article discusses the links between investment andthe environment and the dilemma facing developing countries in their efforts toregulate the environmental impacts of investment more strictly. More specifically, itexplains how countries‟ interest in remaining competitive in attracting investmentaffects the integrity of the environment. It also indicates a lack of institutionalcapacity to regulate investment, and the existence of a power imbalance betweendeveloping counties and companies (particularly multinationals) as factorsjeopardizing the environment. It highlights the importance of effective policymeasures to reap the benefits of investment and protect the environment at the sametime. Finally, the article argues that countries need to introduce environmentalregulatory systems that give room for different actors—governments, NGOs, thecommunity, and business enterprises—to work together to control the environmentalimpacts of investment, presenting an alternative to the conventional command-andcontrol approach. It elaborates how stakeholders‟ involvement, and specifically thatof companies, is vital to ease developing countries‟ anxiety about losing the inflow of direct investment due to strict environmental regulation.